Teoria Podobieństwa Zjawisk Termoelastoplastycznych - Madejski, J. (Engineering Transactions, 1957)
This paper contains a derivation of criteria for describing thermo-elastoplastic states in bodies of similar shape and load. The dynamic theory of plasticity, proposed by the author in [1], is assumed as a basis. For example, some solutions given in paper [1] are presented in a criterial form, by using certain dimensionless groups. Finally, an example of practical application of the principle of similarity for generalizing experimental data is presented. The example concerning the longtime strength of superheater tubes is based on experimental results obtained by K a t z.